(untitled) (Revista Latino-Americana de Enfermagem, 2019)
Objective: to identify the predictive variables or the massive transfusion triggers in severely traumatized patients through the existing scales. Method: a review of the literature was carried out using the Scoping Review method across the electronic databases CINAHL, MEDLINE, LILACS, the Cochrane and IBECS libraries, and the Google Scholar search tool. Results: in total, 578 articles were identified in the search and the 36 articles published in the last ten years were included, of which 29 were original articles and 7 review articles. From the analysis, scales for massive transfusion and their predictive triggers were examined. Conclusion: the absence of universal criteria regarding the massive transfusion triggers in traumatized patients has led to the development of different scales, and the studies on their validation are considered relevant for the studies about when to initiate this strategy.